Simulation and factitious malingering - Wójcicka, Anna; Grzywa, Anna; Celiński, Rafał (Current Problems of Psychiatry, 2011)
Reasons, why people simulate a disease are various, including expected financial benefits, the need to feel the sympathy of other people, or mundane feeling of pleasure caused by cheating another person. The main aim of this article is to analyse the possible strategies of detecting and diagnosing the simulation and its alike various forms of Münchausen syndrome – both by proxy and similar alleged disease per procura. Münchausen syndrome, classified as psychical disease, is characterised by conscious creating own pathological symptoms. The prevalence of this disorder is unknown. It is estimated that around 5-10% of all hospital admissions is due to simulated symptoms. The aetiology of Münchausen syndrome has not been explained so far either. In the specialist literature it is being underlined that the crucial importance in development of this disorder is played by both the somatic as well as psychical factors. This syndrome is rarely diagnosed and identified and poses a real challenge to the health care staff, because it causes a lot of diagnostic difficulties. The core importance in the diagnosis play the good knowledge of clinical patterns and symptoms of this disease, among which there is purposeful inducing of psychical or somatic syndromes in self, pathological lying and frequent changing of hospitalisation place. Particularly important is carefully taken history as well as insightful conversation and observation of the patient with often incompatible results of additional examinations.